Stanniocalcin 1a regulates organismal calcium balance and survival by suppressing Trpv6 expression and inhibiting IGF signaling in zebrafish - Li, Shuang; Li, Helena; Wang, Zhengyi; Duan, Cunming (Frontiers in Endocrinology, 2023)
Stanniocalcin 1 (Stc1) is well known for its role in regulating calcium uptake in fish by acting on ionocytes or NaR cells. A hallmark of NaR cells is the expression of Trpv6, a constitutively open calcium channel. Recent studies in zebrafish suggest that genetical deletion of Stc1a and Trpv6 individually both increases IGF signaling and NaR cell proliferation. While trpv6-/- fish suffered from calcium deficiency and died prematurely, stc1a-/- fish had elevated body calcium levels but also died prematurely. The relationship between Stc1a, Trpv6, and IGF signaling in regulating calcium homeostasis and organismal survival is unclear. Here we report that loss of Stc1a increases Trpv6 expression in NaR cells in an IGF signaling-dependent manner. Treatment with CdCl2, a Trpv6 inhibitor, reduced NaR cell number in stc1a-/- fish to the sibling levels. Genetic and biochemical analysis results suggest that Stc1a and Trpv6 regulate NaR cell proliferation via the same IGF pathway. Alizarin red staining detected abnormal calcium deposits in the yolk sac region and kidney stone-like structures in stc1a-/- fish. Double knockout or pharmacological inhibition of Trpv6 alleviated these phenotypes, suggesting that Stc1a inhibit epithelial Ca2+ uptake by regulating Trpv6 expression and activity. stc1a-/- mutant fish developed cardiac edema, body swelling, and died prematurely. Treatment of stc1a-/- fish with CdCl2 or double knockout of Trpv6 alleviated these phenotypes. These results provide evidence that Stc1a regulates calcium homeostasis and organismal survival by suppressing Trpv6 expression and inhibiting IGF signaling in ionocytes.